Bridging the resolution gap: correlative super-resolution imaging - Dobbie, IM (Nature Research, 2019)
This month’s Under the Lens discusses progress towards bridging the resolution gap in correlative super-resolution light and electron microscopy, and highlights its application for visualizing bacterial infections.